Accurate contrast determination for X‐ray speckle visibility spectroscopy. (19th June 2020) - Sun, Yanwen; Montana-Lopez, Jordi; Fuoss, Paul; Sutton, Mark; Zhu, Diling
Abstract : A numerical model that can mimic closely the behavior of real X‐ray detectors in the context of X‐ray speckle visibility spectroscopy is described. Using this model, this work investigates the origin of discrepancies between commonly used photon locating algorithms and proposes a calibration routine to resolve the discrepancy. Abstract : X‐ray speckle visibility spectroscopy using X‐ray free‐electron lasers has long been proposed as a probe of fast dynamics in noncrystalline materials. In this paper, numerical modeling is presented to show how the data interpretation of visibility spectroscopy can be impacted by the nonidealities of real‐life X‐ray detectors. Using simulated detector data, this work provides a detailed analysis of the systematic errors of several contrast extraction algorithms in the context of low‐count‐rate X‐ray speckle visibility spectroscopy and their origins are discussed. Here, it was found that the finite detector charge cloud and pixel size lead to an unavoidable `degeneracy' in photon position determination, and that the contrasts extracted using different algorithms can all be corrected by a simple linear model. The results suggest that experimental calibration of the correction coefficient at the count rate of interest is possible and essential. This allows computationally lightweight algorithms to be implemented for on‐the‐fly analysis.